Environment and Renewable Natural Resources in Angola : Opportunities to Diversify the National Economy, Generate Income for Local Communities, Enhance Environmental Management Capacity and Build Resilience to Climate Change - World Bank (World Bank, Washington, DC, 2019)
This report presents the economic potential of renewable natural resources (forests, wildlife and fisheries), and identifies opportunities for enhancing the sectors’ contribution to both the national and local economies in Angola (Section two). Given the strong focus of the ongoing CPF on economic diversification, the report focuses on these selected sectors whose sustainable use offers opportunities for diversifying the economy, creating jobs and improving local livelihoods. In light of the implementation of the World Bank’s new Environmental and Social Framework (ESF), the report assesses the current national legislation and policy framework for assessing and mitigating potential environmental and social risks and impacts caused by investment projects and proposes opportunities which can support in strengthening the national capacity in order to facilitate project design and implementation following the World Bank’s due diligence (Section three). The report then assesses the current policy and institutional framework for addressing climate change in Angola and proposes opportunities to support these (Section four). Finally, the report concludes by proposing opportunities for World Bank engagement in the sectors selected (forests, wildlife and fisheries), as well as in enhancing environmental management capacity and building resilience to climate change.A World Bank mission was organized to Angola in October 2018, and collected data relevant to the study and discussed with government officials, development partners, CSOs, and other relevant stakeholders the status, priorities, and potential opportunities for each of the sectors considered. This report uses data and information collected during the mission and shared by government institutions and other stakeholders, as well as data and literature that are publicly available. The report also uses information collected as part of the World Bank report on Central African Coastal Fisheries (which assessed the fisheries sector of countries within the Regional Commission of Fisheries of Gulf of Guinea [Commission Régionale des Pêches du Golfe de Guinée, COREP]—of which Angola is a part), and for which a World Bank mission was organized in May 2018.